The Influence Of Motivation And Remuneration On Employee Performance With Leadership Style As A Moderating Variable - Darmawan, Andi; Hariyanto, Eko; Budi, Suryo (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Factors that can affect employee performance, namely motivation and remuneration. One of the other important elements is leadership. This study aims to analyze the influence of motivation and remuneration on employee performance with leadership style as a moderating variable. This research is quantitative research. The population in this study was all employees in the ranks of the Technical Implementation Unit in Nusakambangan who came from 9 work units. Determination of respondents using purposive sampling method. The sample in this study is part of the total employee population in the ranks of the Technical Implementation Unit in Nusakambangan taken from each work unit. Research data were obtained through questionnaires. The data analysis technique used is a qualitative technique, namely an interactive analysis technique using the PLS (Partial Least Square) analysis tool. Based on the analysis and discussion, the following conclusions can be drawn: (1) Motivation has a positive effect on employee performance; (2) Remuneration has a positive effect on employee performance; (3) Leadership style does not moderate the influence of motivation on employee performance; (4) Leadership style does not moderate the effect of Remuneration on employee performance. Keywords: Motivation, Remuneration, Leadership Style, Moderating, Employees